A gradient structure positive electrode material and its preparation method and use

By setting transition components in the lithium cobalt phosphate positive electrode material to form a gradient structure, the concentrations of active ingredients and protective components gradually transition from the inside to the outside, the problems of poor conductivity and instability of solid-liquid interface of lithium cobalt phosphate positive electrode material are solved, and high rate performance and cyclic stability are achieved.

CN115663178BActive Publication Date: 2025-03-04EVE POWER CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211357348.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-01
Publication Date
2025-03-04
Estimated Expiration
2042-11-01

AI Technical Summary

Technical Problem

The existing lithium cobalt phosphate positive electrode materials have problems such as poor conductivity, high working voltage, easy decomposition of the electrolyte, unstable solid-liquid interface, and material decomposition caused by electrolyte erosion, which affects its charge and discharge performance and cycle life.

Method used

By setting the transition component LiCo1-y-zVzNyPO4 between the active ingredient LiCo1-xMxPO4 and the protective ingredient Li3V2 (PO4)3, the concentration of the active ingredient gradually decreases from the inside to the outside, and the concentration of the protective ingredient gradually increases, thereby enhancing the bonding between the two and the smoothness of the transition interface, and improving the efficiency of the charge transport and ion diffusion process.

Benefits of technology

It is achieved without destroying the lattice structure of the active ingredient, strengthening its bonding with the protective component, improving the rate performance and cycle stability of the positive electrode material, and enhancing the stability of the solid-liquid interface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115663178B_ABST
    Figure CN115663178B_ABST
Patent Text Reader

Abstract

The present invention provides a gradient structure positive electrode material and a preparation method and use thereof. By setting a transition component between the active component and the protective component, the concentration of the active component gradually decreases from the inside to the outside of the positive electrode material, while the concentration of the protective component gradually increases. The gradual transition of the concentration strengthens the binding of the active component and the protective component, making the transition interface between the two smoother, which is conducive to improving the charge transmission and ion diffusion process; the protective component with a higher concentration on the outside can prevent the active component inside from directly contacting the electrolyte, thereby improving the stability of the solid-liquid interface; and the protective component is a fast ion conductor with excellent electrochemical activity and voltage platform, and when its concentration gradually decreases toward the inside, it will not cause serious capacity loss to the positive electrode material; therefore, the performance of the active component can be fully exerted, and the resulting gradient structure positive electrode material has excellent rate performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion batteries and relates to a gradient structure positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are increasingly used in small portable devices, new energy vehicles, energy storage and other fields. In order to cope with more usage scenarios, lithium-ion batteries require higher energy density, and the specific capacity and voltage of the positive electrode material will directly affect the specific energy of the battery. At present, the positive electrode materials used in lithium-ion batteries include: layered materials such as lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, etc.; spinel structure materials such as lithium manganese oxide and lithium nickel manganese oxide, etc.; and olivine structure materials such as lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, etc. Among them, phosphate-based positive electrode materials are widely used in the field of new energy vehicles due to their excellent safety performance and cycle performance. As a leader in the phosphate system, the voltage platform of lithium cobalt phosphate positive electrode material is 4.8V vs.Li + / Li, its theoretical energy density is about 800Wh / kg, which is nearly 40% higher than that of lithium iron phosphate positive electrode material.

[0003] However, lithium cobalt phosphate cathode materials also have some disadvantages: for example, (1) poor electrical conductivity; (2) high operating voltage, easy decomposition of electrolyte, resulting in instability of solid-liquid interface; (3) corrosion of electrolyte on materials, resulting in decomposition of active materials. These will cause loss of charge and discharge performance and cycle life of lithium cobalt phosphate cathode materials.

[0004] In order to overcome the technical problems existing in phosphate-based positive electrode materials, existing technical solutions include: (1) nano-sizing phosphate-based positive electrode materials to improve their fast charge and discharge capabilities and rate performance. For example, CN103956486A discloses a method for preparing a nanofiber-shaped cobalt lithium phosphate positive electrode material, comprising dissolving cobalt salt, lithium salt, phosphate, and high molecular polymer in deionized water, stirring the resulting solution evenly and then standing it until it is clarified; then performing electrostatic spinning; calcining the resulting spinning product under an inert atmosphere, and after the calcination reaction is completed, waiting for the material to cool to room temperature, taking out the product to obtain a cobalt lithium phosphate positive electrode material with a nanofiber morphology; the resulting product has a nanofiber morphology, which increases the contact between the material and the electrolyte and is beneficial to the transmission of lithium ions. At the same time, the material and carbon form a composite structure, which improves the conductivity of the material; however, the phosphate-based positive electrode material after nano-sizing is prone to more intense side reactions at the interface with the electrolyte due to its increased specific surface area, especially as the use temperature increases, it is more likely to cause the structure of the phosphate-based positive electrode material to be destroyed. (2) Carbon coating of phosphate-based positive electrode materials can improve their conductivity, accelerate electron transport, and promote lithium ion diffusion, especially at high charge and discharge rates, which can greatly reduce the possibility of their own structure being destroyed under large lithium ion flux. For example, CN105576204A discloses a graphene composite carbon-coated lithium cobalt phosphate material, which is composed of lithium cobalt phosphate, graphene and carbon. The lithium cobalt phosphate, graphene and carbon are in situ symbiotically composited, and the good flexibility of graphene is utilized to achieve better combination with lithium cobalt phosphate. The three-dimensional conductive network is formed by graphene and in situ generated carbon, which improves the electrochemical performance of lithium cobalt phosphate. The obtained lithium cobalt phosphate positive electrode material has a high discharge specific capacity and good rate performance. However, after the phosphate-based positive electrode material is carbon-coated, there is still a problem of lattice interface destruction caused by reaction with free acid in the electrolyte.

[0005] From the above, it can be seen that there is still a need to develop a new lithium cobalt phosphate positive electrode material, which can effectively overcome the defects of phosphate-based positive electrode materials without destroying their structure, so that the performance of lithium cobalt phosphate can be fully utilized, which is of great significance for promoting the development of lithium-ion batteries containing lithium cobalt phosphate positive electrode materials. Summary of the invention

[0006] In view of the problems existing in the prior art, the object of the present invention is to provide a gradient structure positive electrode material and a preparation method and use thereof, by 1-x M x PO 4 And protective component Li 3 V 2 (PO 4 ) 3 Set the transition component LiCo between 1-y-z V z Ny PO 4 , so that the concentration of the active ingredient gradually decreases from the inside to the outside of the positive electrode material, while the concentration of the protective ingredient gradually increases. The present invention strengthens the binding of the active ingredient and the protective ingredient through the gradual transition of concentration, making the transition interface between the two smoother, which is conducive to improving the charge transfer and ion diffusion process; the protective ingredient with a higher concentration on the outside can prevent the active ingredient inside from directly contacting the electrolyte, thereby improving the stability of the solid-liquid interface; and the protective ingredient is a fast ion conductor with excellent electrochemical activity and voltage platform, and when its concentration gradually decreases toward the inside, it will not cause serious capacity loss to the positive electrode material; therefore, the performance of the active ingredient can be fully exerted, and the resulting gradient structure positive electrode material has excellent rate performance and cycle stability.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a gradient structure positive electrode material, wherein the gradient structure positive electrode material comprises an active component and a protective component encapsulating the active component; from the inside to the outside of the gradient structure positive electrode material, the concentration of the active component gradually decreases, and the concentration of the protective component gradually increases;

[0009] The gradient structure positive electrode material further includes a transition component, which is disposed between the active component and the protective component and diffuses toward the active component and the protective component respectively;

[0010] The active ingredient includes LiCo 1-x M x PO 4 , wherein M is any one of Ti, Zr, Al or a combination of at least two thereof, 0.01≤x≤0.1; the protective component includes Li 3 V 2 (PO 4 ) 3 ; The transition component includes LiCo 1-y-z V z N y PO 4 , wherein N is any one of Ti, Zr, and Al or a combination of at least two thereof, 0.01≤y≤0.1, 0.2≤z≤0.45.

[0011] The present invention provides the transition component LiCo in the gradient structure positive electrode material. 1-y-z V z N y PO 4 , the active ingredient LiCo 1-x M x PO4 The concentration of the protective component Li 3 V 2 (PO 4 ) 3 The concentration gradually increases, and the binding between the active ingredient and the protective ingredient and the smoothness of the transition zone are further enhanced; the transition component is formed by further replacing a part of the cobalt element with the vanadium element on the basis of the active ingredient, and its cobalt content is lower than that of the active ingredient, and the vanadium content is lower than that of the protective ingredient. Therefore, it can support the mutual diffusion between the active ingredient and the protective ingredient, effectively optimize the internal transition zone, thereby strengthening the binding with the protective ingredient without destroying the lattice structure of the active ingredient, making the transition interface between the two smoother, which is conducive to improving the charge transfer and ion diffusion process.

[0012] The active ingredient selected in the present invention is lithium cobalt phosphate doped LiCo 1-x M x PO 4 , doping creates defects inside the crystal, which are beneficial to Li + The diffusion of the doped element is also promoted, and because the charge valence state of the doped element is different from that of the metal element in the original lattice, a charge difference is generated, and cation vacancies are formed through the charge compensation mechanism, which improves the conductivity of the material and improves the rate performance of the material.

[0013] The present invention provides a protective component Li with a higher external concentration. 3 V 2 (PO 4 ) 3 , effectively preventing the internal active ingredients from directly contacting the electrolyte, improving the stability of the solid-liquid interface, and helping to improve the cycle stability of the positive electrode material; Li 3 V 2 (PO 4 ) 3 It is a fast ion conductor material that increases the Li + The transport channel improves the ionic conductivity of the material, and compared with other non-electrochemically active fast ion conductors, Li 3 V 2 (PO 4 ) 3 It has good electrochemical activity and voltage platform, and will not cause serious capacity loss to the positive electrode material when its concentration gradually decreases inward.

[0014] With the cooperation of the active component, transition component and protective component of the specific structure of the present invention, the capacity and voltage performance of the active component can be fully exerted, and the obtained gradient structure positive electrode material has excellent rate performance and cycle stability.

[0015] It should be noted that the value of x is 0.01≤x≤0.1, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1, the value of y is 0.01≤y≤0.1, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1, and the value of z is 0.2≤z≤0.45, such as 0.2, 0.25, 0.3, 0.35, 0.4 or 0.45, but is not limited to the listed values, and other values ​​not listed within the above numerical range are equally applicable.

[0016] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0017] As a preferred technical solution of the present invention, from the inside to the outside of the gradient structure positive electrode material, the concentration of the active component gradually decreases from 100% to 0, and the concentration of the protective component gradually increases from 0 to 100%.

[0018] The present invention preferably allows only protective components to exist on the outermost portion of the obtained gradient structure positive electrode material, thereby better protecting the active components and preventing the electrolyte from corroding the internal active components.

[0019] Preferably, the mass of the active ingredient accounts for 90 to 98 wt% of the mass of the gradient structure positive electrode material, for example 90 wt%, 91 wt%, 92 wt%, 93 wt%, 94 wt%, 95 wt%, 96 wt%, 97 wt% or 98 wt%, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0020] Preferably, the mass of the protective component accounts for 2 to 10 wt% of the mass of the gradient structure positive electrode material, for example 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt% or 8wt%, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0021] Preferably, the mass of the active ingredient accounts for 75 to 88 wt% of the mass of the gradient structure positive electrode material, for example 75wt%, 76wt%, 77wt%, 78wt%, 79wt%, 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt% or 88wt%, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0022] Preferably, the mass of the protective component accounts for 2 to 5wt% of the mass of the gradient structure positive electrode material, for example 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0023] Preferably, the mass of the transition component accounts for 10 to 20 wt% of the mass of the gradient structure positive electrode material, for example 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt% or 20 wt%, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0024] In a second aspect, the present invention provides a method for preparing the gradient structure positive electrode material according to the first aspect, the method comprising the following steps:

[0025] (1) adding a phosphorus source to an aqueous solution containing a cobalt source and a metal M source in a molar ratio of (1-x):1, and heating the solution to react to obtain a first precursor material; 0.01≤x≤0.1;

[0026] (2) adding the first precursor material obtained in step (1) and the phosphorus source to an aqueous solution containing a cobalt source, a vanadium source and a metal N source in a molar ratio of (1-yz):z:y, and heating the mixture to react to obtain a second precursor material; 0.01≤y≤0.1, 0.2≤z≤0.45;

[0027] (3) adding the second precursor material obtained in step (2) and the phosphorus source to the aqueous solution containing the vanadium source, and heating the mixture to react to obtain a third precursor material;

[0028] (4) Mixing the lithium source with the third precursor material obtained in step (3) and sintering the mixture under an inert atmosphere to obtain a gradient structure positive electrode material.

[0029] In order to form the gradient structure positive electrode material described in the present invention, in the preparation method of the present invention, a precursor is first prepared, such as a first precursor material, a second precursor material and a third precursor material, and finally only one high-temperature sintering is performed. Active components, transition components and protective components with varying concentrations are formed in situ through the diffusion of various elements during the high-temperature sintering. At the same time, since only one sintering is performed, the damage to the lattice structure of the active component is avoided, thereby maintaining the performance of the active component itself to the greatest extent.

[0030] As a preferred technical solution of the present invention, the temperature of the heating reaction in step (1), step (2) and step (3) is independently selected from 20 to 50°C, for example, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0031] Preferably, the time for the heating reaction in step (1), step (2) and step (3) is independently selected from 3 to 8 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0032] Preferably, the preparation method further comprises washing and drying the obtained first precursor material, second precursor material and third precursor material in step (1), step (2) and step (3) respectively.

[0033] Preferably, the washing comprises washing with water until the pH is neutral.

[0034] Preferably, the drying is performed under vacuum.

[0035] Preferably, the drying temperature is 80-100°C, for example 80°C, 85°C, 90°C, 95°C or 100°C, and the drying time is 20-30h, for example 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h or 30h, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0036] As a preferred technical solution of the present invention, the sintering in step (4) includes first performing a first sintering and then performing a second sintering.

[0037] Preferably, the first sintering temperature is 200-300°C, for example 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, and the time is 3-5h, for example 3h, 3.5h, 4h, 4.5h or 5h, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0038] Preferably, the second sintering temperature is 600-800°C, for example 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C or 800°C, and the time is 8-15h, for example 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0039] Preferably, the inert atmosphere in step (4) comprises any one of nitrogen, helium or argon, or a combination of at least two of them. Typical but non-limiting examples of the combination include a combination of nitrogen and helium, a combination of nitrogen and argon, and a combination of helium and argon.

[0040] As a preferred technical solution of the present invention, the cobalt source includes any one of cobalt sulfate, cobalt chloride, cobalt nitrate or cobalt oxalate, or a combination of at least two of them. Typical but non-limiting examples of the combination include a combination of cobalt sulfate and cobalt chloride, a combination of cobalt sulfate and cobalt nitrate, a combination of cobalt sulfate and cobalt oxalate, a combination of cobalt chloride and cobalt nitrate, a combination of cobalt chloride and cobalt oxalate, and a combination of cobalt nitrate and cobalt oxalate.

[0041] Preferably, the metal M source includes any one of titanium sulfate, titanium chloride, titanium nitrate, zirconium sulfate, zirconium chloride, zirconium nitrate, aluminum sulfate, aluminum chloride or aluminum nitrate, or a combination of at least two thereof. Typical but non-limiting examples of the combination include a combination of titanium sulfate and titanium chloride, a combination of titanium sulfate and titanium nitrate, a combination of titanium sulfate and zirconium sulfate, a combination of titanium sulfate and zirconium chloride, a combination of titanium sulfate and zirconium nitrate, a combination of titanium sulfate and aluminum sulfate, a combination of titanium sulfate and aluminum chloride, a combination of titanium sulfate and aluminum nitrate, and a combination of zirconium nitrate and aluminum nitrate.

[0042] Preferably, the phosphorus source comprises ammonium phosphate and / or diammonium phosphate.

[0043] Preferably, the vanadium source comprises ammonium metavanadate and / or vanadium pentoxide.

[0044] Preferably, the lithium source comprises lithium hydroxide and / or lithium carbonate.

[0045] As a preferred technical solution of the present invention, the metal N source in step (2) and the metal M source in step (1) are the same material.

[0046] Preferably, the cobalt source in step (2) is the same material as the cobalt source in step (1).

[0047] Preferably, the vanadium source in step (2) is the same material as the vanadium source in step (1).

[0048] Preferably, the phosphorus sources in step (1), step (2) and step (3) are of the same material.

[0049] In a third aspect, the present invention provides a positive electrode sheet containing the gradient structure positive electrode material described in the first aspect or the gradient structure positive electrode material obtained by the preparation method described in the second aspect.

[0050] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet described in the third aspect.

[0051] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0052] (1) The present invention adopts the gradient structure positive electrode material by adding the active component LiCo 1-x M x PO 4 And protective component Li 3 V 2 (PO 4 ) 3 Set the transition component LiCo between 1-y-z V z N y PO 4 , so that the concentration of the active ingredient gradually decreases from the inside to the outside, and the concentration of the protective ingredient gradually increases, thereby strengthening the binding with the protective ingredient without destroying the lattice structure of the active ingredient, making the transition interface between the two smoother, which is conducive to improving the charge transfer and ion diffusion process; the protective ingredient with a higher concentration on the outside can prevent the active ingredient inside from directly contacting the electrolyte, thereby improving the stability of the solid-liquid interface; and Li 3 V 2 (PO 4 ) 3 The fast ion conductor with excellent electrochemical activity and voltage platform will not cause serious capacity loss to the positive electrode material when its concentration gradually decreases toward the inside; therefore, the performance of the active component can be fully exerted, and the obtained gradient structure positive electrode material has excellent rate performance and cycle stability;

[0053] (2) The active ingredient of the present invention is doped lithium cobalt phosphate LiCo 1-x M x PO 4 The doping process creates defects inside the crystal, which are beneficial to Li + The diffusion of the doped element and the metal element in the original lattice is different in charge valence, resulting in a charge difference. Therefore, cation vacancies are formed through the charge compensation mechanism, which improves the conductivity of the material and improves the rate performance of the material.

[0054] (3) The present invention first prepares a doped precursor material (first precursor material) or a multi-layer coated doped precursor material (second precursor material and third precursor material), and then synthesizes a doped lithium cobalt phosphate positive electrode material with a gradient structure through a one-step high-temperature sintering. While supporting the synthesis of the gradient structure positive electrode material described in the present invention, it avoids the damage to the crystal structure of the doped lithium cobalt phosphate caused by high temperature after multiple sintering in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 Schematic diagram of the distribution of cobalt and vanadium elements in the cross section of the gradient structure positive electrode material obtained in Example 1 of the present invention;

[0056] Figure 2 It is a schematic diagram of the distribution of cobalt and vanadium elements in the cross section of the positive electrode material obtained in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0057] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0058] Example 1

[0059] This embodiment provides a gradient structure positive electrode material, wherein the positive electrode material includes an active component LiCo 0.95 Ti 0.05 PO 4 , a protective component Li encapsulating the active ingredient 3 V 2 (PO 4 ) 3 and a transition component LiCo disposed between the active component and the protective component and diffused toward the active component and the protective component, respectively. 0.6 V 0.37 Ti 0.03 PO 4 ; From the inside to the outside of the positive electrode material, the concentration of the active component gradually decreases, and the concentration of the protective component gradually increases; and the mass of the active component, the protective component and the transition component account for 82wt%, 4wt% and 14wt% of the mass of the positive electrode material respectively;

[0060] The preparation method of the gradient structure positive electrode material comprises the following steps:

[0061] (1) adding ammonium phosphate to an aqueous solution containing cobalt nitrate and titanium nitrate in a molar ratio of 0.95:0.05, stirring continuously, heating at 35° C. for reaction for 5 h, then filtering the product, washing with water until the pH is neutral, and vacuum drying at 90° C. for 25 h to obtain a first precursor material;

[0062] (2) adding the first precursor material obtained in step (1) and ammonium phosphate to an aqueous solution containing cobalt nitrate, ammonium metavanadate and titanium nitrate in a molar ratio of 0.6:0.37:0.03, stirring continuously, heating at 35° C. for reaction for 5 h, then filtering the product, washing with water until the pH is neutral, and vacuum drying at 90° C. for 25 h to obtain a second precursor material;

[0063] (3) adding the second precursor material obtained in step (2) and ammonium phosphate to the aqueous solution containing ammonium metavanadate, stirring continuously, heating the reaction at 35° C. for 5 h, then filtering the product, washing with water until the pH is neutral, and vacuum drying at 90° C. for 25 h to obtain a third precursor material;

[0064] (4) After the lithium hydroxide and the third precursor material obtained in step (3) are evenly mixed, the mixture is first sintered at 250° C. for 4 h under the protection of an argon atmosphere, and then second sintered at 700° C. for 11 h to obtain a gradient structure positive electrode material.

[0065] Example 2

[0066] This embodiment provides a gradient structure positive electrode material, wherein the positive electrode material includes an active component LiCo 0.99 Al 0.01 PO 4 , a protective component Li encapsulating the active ingredient 3 V 2 (PO 4 ) 3 and a transition component LiCo disposed between the active component and the protective component and diffused toward the active component and the protective component, respectively. 0.58 V 0.21 Al 0.01 PO 4 ; From the inside to the outside of the positive electrode material, the concentration of the active component gradually decreases, and the concentration of the protective component gradually increases; and the mass of the active component, the protective component and the transition component account for 75wt%, 5wt% and 20wt% of the mass of the positive electrode material respectively;

[0067] The preparation method of the gradient structure positive electrode material comprises the following steps:

[0068] (1) adding ammonium phosphate to an aqueous solution containing cobalt oxalate and aluminum nitrate in a molar ratio of 0.99:0.01, stirring continuously, heating at 20° C. for reaction for 8 h, then filtering the product, washing with water until the pH is neutral, and vacuum drying at 80° C. for 30 h to obtain a first precursor material;

[0069] (2) adding the first precursor material obtained in step (1) and ammonium phosphate to an aqueous solution containing cobalt oxalate, ammonium metavanadate and aluminum nitrate in a molar ratio of 0.58:0.21:0.01, stirring continuously, heating at 20° C. for 8 h, then filtering the product, washing with water until the pH is neutral, and vacuum drying at 80° C. for 30 h to obtain a second precursor material;

[0070] (3) adding the second precursor material obtained in step (2) and ammonium phosphate to the aqueous solution containing vanadium pentoxide, continuously stirring, heating and reacting at 20° C. for 8 h, then filtering the product, washing with water until the pH is neutral, and vacuum drying at 80° C. for 30 h to obtain a third precursor material;

[0071] (4) After the lithium carbonate and the third precursor material obtained in step (3) are evenly mixed, a first sintering is performed at 200° C. for 5 h under the protection of an argon atmosphere, and then a second sintering is performed at 600° C. for 15 h to obtain a gradient structure positive electrode material.

[0072] Example 3

[0073] This embodiment provides a gradient structure positive electrode material, wherein the positive electrode material includes an active component LiCo 0.93 Zr 0.07 PO 4 , a protective component Li encapsulating the active ingredient 3 V 2 (PO 4 ) 3 and a transition component LiCo disposed between the active component and the protective component and diffused toward the active component and the protective component, respectively. 0.65 V 0.3 Zr 0.05 PO 4 ; From the inside to the outside of the positive electrode material, the concentration of the active component gradually decreases, and the concentration of the protective component gradually increases; and the mass of the active component, the protective component and the transition component account for 84wt%, 3.5wt% and 12.5wt% of the mass of the positive electrode material respectively;

[0074] The preparation method of the gradient structure positive electrode material comprises the following steps:

[0075] (1) adding ammonium dihydrogen phosphate to an aqueous solution containing cobalt chloride and zirconium nitrate in a molar ratio of 0.93:0.07, stirring continuously, heating at 40° C. for 7 h, then filtering the product, washing with water until the pH is neutral, and vacuum drying at 95° C. for 27 h to obtain a first precursor material;

[0076] (2) adding the first precursor material obtained in step (1) and ammonium dihydrogen phosphate to an aqueous solution containing cobalt chloride, ammonium metavanadate and zirconium nitrate in a molar ratio of 0.65:0.3:0.05, stirring continuously, heating at 40° C. for 7 h, then filtering the product, washing with water until the pH is neutral, and vacuum drying at 95° C. for 27 h to obtain a second precursor material;

[0077] (3) adding the second precursor material obtained in step (2) and ammonium dihydrogen phosphate to the aqueous solution containing vanadium pentoxide, stirring continuously, heating at 40° C. for reaction for 7 h, then filtering the product, washing with water until the pH is neutral, and vacuum drying at 95° C. for 27 h to obtain a third precursor material;

[0078] (4) After the lithium hydroxide and the third precursor material obtained in step (3) are evenly mixed, a first sintering is performed at 230° C. for 4.5 h under the protection of a mixed atmosphere of argon and nitrogen, and a second sintering is performed at 750° C. for 10 h to obtain a gradient structure positive electrode material.

[0079] Example 4

[0080] This embodiment provides a gradient structure positive electrode material, wherein the positive electrode material includes an active component LiCo 0.9 Al 0.1 PO 4 , a protective component Li encapsulating the active ingredient 3 V 2 (PO 4 ) 3 and a transition component LiCo disposed between the active component and the protective component and diffused toward the active component and the protective component, respectively. 0.47 V 0.44 Al 0.09 PO 4 ; From the inside to the outside of the positive electrode material, the concentration of the active component gradually decreases, and the concentration of the protective component gradually increases; and the mass of the active component, the protective component and the transition component account for 88wt%, 2wt% and 10wt% of the mass of the positive electrode material respectively;

[0081] The preparation method of the positive electrode material comprises the following steps:

[0082] (1) adding ammonium dihydrogen phosphate to an aqueous solution containing cobalt nitrate and aluminum sulfate in a molar ratio of 0.9:0.1, stirring continuously, heating at 50° C. for reaction for 3 h, then filtering the product, washing with water until the pH is neutral, and vacuum drying at 100° C. for 20 h to obtain a first precursor material;

[0083] (2) adding the first precursor material obtained in step (1) and ammonium dihydrogen phosphate to an aqueous solution containing cobalt nitrate, ammonium metavanadate and aluminum sulfate in a molar ratio of 0.47:0.44:0.09, stirring continuously, heating at 50° C. for reaction for 3 h, then filtering the product, washing with water until the pH is neutral, and vacuum drying at 100° C. for 20 h to obtain a second precursor material;

[0084] (3) adding the second precursor material obtained in step (2) and ammonium dihydrogen phosphate to the aqueous solution containing vanadium pentoxide, stirring continuously, heating the reaction at 50° C. for 3 h, then filtering the product, washing with water until the pH is neutral, and vacuum drying at 100° C. for 20 h to obtain a third precursor material;

[0085] (4) After the lithium hydroxide and the third precursor material obtained in step (3) are evenly mixed, the mixture is first sintered at 300° C. for 3 h under the protection of an argon atmosphere, and then second sintered at 800° C. for 8 h to obtain a gradient structure positive electrode material.

[0086] Example 5

[0087] This embodiment provides a gradient structure positive electrode material, in which the active component, protective component and transition component account for 71wt%, 4wt% and 25wt% of the mass of the positive electrode material respectively, and other conditions are exactly the same as those in Embodiment 1.

[0088] Example 6

[0089] This embodiment provides a gradient structure positive electrode material, in which the active component, protective component and transition component account for 76wt%, 4wt% and 20wt% of the mass of the positive electrode material respectively, and other conditions are exactly the same as those in Embodiment 1.

[0090] Example 7

[0091] This embodiment provides a gradient structure positive electrode material, in which the active component, protective component and transition component account for 86wt%, 4wt% and 10wt% of the mass of the positive electrode material respectively, and other conditions are exactly the same as those in Embodiment 1.

[0092] Example 8

[0093] This embodiment provides a gradient structure positive electrode material, in which the active component, protective component and transition component account for 91wt%, 4wt% and 5wt% of the mass of the positive electrode material respectively, and other conditions are exactly the same as those in Embodiment 1.

[0094] Example 9

[0095] This embodiment provides a gradient structure positive electrode material, in which the active component, protective component and transition component account for 83.5wt%, 0.5wt% and 16wt% of the positive electrode material respectively, and other conditions are exactly the same as those in Embodiment 1.

[0096] Example 10

[0097] This embodiment provides a gradient structure positive electrode material, in which the active component, protective component and transition component account for 82wt%, 2wt% and 16wt% of the mass of the positive electrode material respectively, and other conditions are exactly the same as those in Embodiment 1.

[0098] Embodiment 11

[0099] This embodiment provides a gradient structure positive electrode material, in which the active component, protective component and transition component account for 79wt%, 5wt% and 16wt% of the positive electrode material respectively, and other conditions are exactly the same as those in Embodiment 1.

[0100] Example 12

[0101] This embodiment provides a gradient structure positive electrode material, in which the active component, protective component and transition component account for 77.5wt%, 6.5wt% and 16wt% of the positive electrode material respectively, and other conditions are exactly the same as those in Embodiment 1.

[0102] Example 13

[0103] This embodiment provides a positive electrode material with a gradient structure, wherein the positive electrode material has a transition component of LiCo 0.6 V 0.37 Ti 0.03 PO 4 Adjusted to LiCo 0.62 V 0.37 Ti 0.01 PO 4 That is, except that the molar ratio of cobalt nitrate, ammonium metavanadate and titanium nitrate in step (2) of the method for preparing the positive electrode material is adjusted from 0.6:0.37:0.03 to 0.62:0.37:0.01, the other conditions are exactly the same as those in Example 1.

[0104] Embodiment 14

[0105] This embodiment provides a positive electrode material with a gradient structure, wherein the positive electrode material has a transition component of LiCo 0.6 V 0.37 Ti 0.03 PO 4 Adjusted to LiCo 0.58 V0.37 Ti 0.05 PO 4 That is, except that the molar ratio of cobalt nitrate, ammonium metavanadate and titanium nitrate in step (2) of the method for preparing the positive electrode material is adjusted from 0.6:0.37:0.03 to 0.58:0.37:0.05, the other conditions are exactly the same as those in Example 1.

[0106] Embodiment 15

[0107] This embodiment provides a positive electrode material with a gradient structure, wherein the positive electrode material has a transition component of LiCo 0.6 V 0.37 Ti 0.03 PO 4 Adjusted to LiCo 0.53 V 0.37 Ti 0.1 PO 4 That is, except that the molar ratio of cobalt nitrate, ammonium metavanadate and titanium nitrate in step (2) of the method for preparing the positive electrode material is adjusted from 0.6:0.37:0.03 to 0.53:0.37:0.1, the other conditions are exactly the same as those in Example 1.

[0108] Example 16

[0109] This embodiment provides a positive electrode material with a gradient structure, wherein the positive electrode material has a transition component of LiCo 0.6 V 0.37 Ti 0.03 PO 4 Adjusted to LiCo 0.82 V 0.15 Ti 0.03 PO 4 That is, except that the molar ratio of cobalt nitrate, ammonium metavanadate and titanium nitrate in step (2) of the method for preparing the positive electrode material is adjusted from 0.6:0.37:0.03 to 0.82:0.15:0.03, the other conditions are exactly the same as those in Example 1.

[0110] Embodiment 17

[0111] This embodiment provides a positive electrode material with a gradient structure, wherein the positive electrode material has a transition component of LiCo 0.6 V 0.37 Ti 0.03 PO 4 Adjusted to LiCo 0.76 V 0.21 Ti 0.03 PO 4That is, except that the molar ratio of cobalt nitrate, ammonium metavanadate and titanium nitrate in step (2) of the method for preparing the positive electrode material is adjusted from 0.6:0.37:0.03 to 0.76:0.21:0.03, other conditions are exactly the same as those in Example 1.

[0112] Embodiment 18

[0113] This embodiment provides a positive electrode material with a gradient structure, wherein the positive electrode material has a transition component of LiCo 0.6 V 0.37 Ti 0.03 PO 4 Adjusted to LiCo 0.67 V 0.3 Ti 0.03 PO 4 That is, except that the molar ratio of cobalt nitrate, ammonium metavanadate and titanium nitrate in step (2) of the method for preparing the positive electrode material is adjusted from 0.6:0.37:0.03 to 0.67:0.3:0.03, other conditions are exactly the same as those in Example 1.

[0114] Embodiment 19

[0115] This embodiment provides a positive electrode material with a gradient structure, wherein the positive electrode material has a transition component of LiCo 0.6 V 0.37 Ti 0.03 PO 4 Adjusted to LiCo 0.52 V 0.45 Ti 0.03 PO 4 That is, except that the molar ratio of cobalt nitrate, ammonium metavanadate and titanium nitrate in step (2) of the method for preparing the positive electrode material is adjusted from 0.6:0.37:0.03 to 0.52:0.45:0.03, the other conditions are exactly the same as those in Example 1.

[0116] Embodiment 20

[0117] This embodiment provides a positive electrode material with a gradient structure, wherein the positive electrode material has a transition component of LiCo 0.6 V 0.37 Ti 0.03 PO 4 Adjusted to LiCo 0.47 V 0.5 Ti 0.03 PO 4 That is, except that the molar ratio of cobalt nitrate, ammonium metavanadate and titanium nitrate in step (2) of the method for preparing the positive electrode material is adjusted from 0.6:0.37:0.03 to 0.47:0.5:0.03, other conditions are exactly the same as those in Example 1.

[0118] Comparative Example 1

[0119] This comparative example provides a gradient structure positive electrode material, wherein the positive electrode material has a transition component of LiCo 0.6 V 0.37 Ti 0.03 PO 4 Adjusted to LiCo 0.625 V 0.37 Ti 0.005 PO 4 That is, except that the molar ratio of cobalt nitrate, ammonium metavanadate and titanium nitrate in step (2) of the method for preparing the positive electrode material is adjusted from 0.6:0.37:0.03 to 0.625:0.37:0.005, the other conditions are exactly the same as those in Example 1.

[0120] Comparative Example 2

[0121] This comparative example provides a gradient structure positive electrode material, wherein the positive electrode material has a transition component of LiCo 0.6 V 0.37 Ti 0.03 PO 4 Adjusted to LiCo 0.48 V 0.37 Ti 0.15 PO 4 That is, except that the molar ratio of cobalt nitrate, ammonium metavanadate and titanium nitrate in step (2) of the method for preparing the positive electrode material is adjusted from 0.6:0.37:0.03 to 0.48:0.37:0.15, the other conditions are exactly the same as those in Example 1.

[0122] Comparative Example 3

[0123] This comparative example provides a positive electrode material, wherein the positive electrode material comprises an active component LiCo 0.95 Ti 0.05 PO 4 , a protective component Li encapsulating the active ingredient 3 V 2 (PO 4 ) 3 and a transition component LiCo disposed between the active component and the protective component 0.6 V 0.37 Ti 0.03 PO 4 ; and the masses of the active component, the protective component and the transition component account for 82wt%, 4wt% and 14wt% of the mass of the positive electrode material respectively;

[0124] The preparation method of the positive electrode material comprises the following steps:

[0125] (1) adding ammonium phosphate to an aqueous solution containing cobalt nitrate and titanium nitrate in a molar ratio of 0.95:0.05, stirring continuously, heating at 35° C. for reaction for 5 h, then filtering the product, washing with water until the pH is neutral, vacuum drying at 90° C. for 25 h, and then sintering at 750° C. for 3 h to obtain a first material;

[0126] (2) adding the first material obtained in step (1) and ammonium phosphate to an aqueous solution containing cobalt nitrate, ammonium metavanadate and titanium nitrate in a molar ratio of 0.6:0.37:0.03, stirring continuously, heating at 35° C. for reaction for 5 h, then filtering the product, washing with water until the pH is neutral, vacuum drying at 90° C. for 25 h, and then sintering at 750° C. for 3 h to obtain an intermediate material;

[0127] (3) adding the intermediate material obtained in step (2) and ammonium phosphate to an aqueous solution containing ammonium metavanadate, stirring continuously, heating the mixture at 35° C. for 5 h, and then filtering the product, washing with water until the pH value is neutral, and vacuum drying the mixture at 90° C. for 25 h to obtain a precursor material;

[0128] (4) After the lithium hydroxide and the precursor material obtained in step (3) are evenly mixed, the mixture is first sintered at 250° C. for 4 h under the protection of an argon atmosphere, and then second sintered at 700° C. for 11 h to obtain a positive electrode material.

[0129] Comparative Example 4

[0130] This comparative example provides a positive electrode material, which does not contain transition components and includes active components LiCo 0.95 Ti 0.05 PO 4 and a protective component Li encapsulating the active ingredient 3 V 2 (PO 4 ) 3 ; and the mass of the active ingredient and the protective ingredient account for 94wt% and 6wt% of the mass of the positive electrode material respectively; the positive electrode material is a core-shell structure.

[0131] The positive electrode materials obtained in each embodiment and comparative example were made into lithium secondary batteries according to the following method and tested.

[0132] 1. Preparation of lithium secondary batteries

[0133] The obtained positive electrode material, a conductive agent (Super PTM) and a polyvinylidene fluoride (PVDF) binder were respectively mixed in an N-methylpyrrolidone (NMP) solvent at a weight ratio of 90:5:5 to prepare a positive electrode mixture, and the mixture was applied on an aluminum foil, and the obtained product was dried and then roll-pressed to prepare a positive electrode;

[0134] Artificial graphite, a conductive agent (Super PTM), carboxymethyl cellulose and styrene-butadiene rubber are mixed into NMP at a weight ratio of 92:4:2:2 to prepare a negative electrode mixture, the negative electrode mixture is coated on a copper foil, the obtained product is dried, and then roll-pressed to prepare a negative electrode;

[0135] An electrode assembly was prepared by placing a porous polyethylene separator between the positive electrode and the negative electrode prepared above, the electrode assembly was placed in a shell, and then an electrolyte was injected into the shell to prepare a lithium secondary battery. The electrolyte was prepared by dissolving 1.15M lithium hexafluorophosphate in an organic solvent formed by ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) (mixing volume ratio of EC / DMC / EMC=3 / 4 / 3).

[0136] 2. Testing of cathode material performance

[0137] The lithium secondary battery was charged at 1C under constant current / constant voltage (CC / CV) conditions at 25° C. until 4.2 V / 0.05 C, and then discharged to 3.0 V using 5C under constant current (CC) conditions, and the discharge specific capacity was calculated;

[0138] The lithium secondary battery was charged at 1C to 4.2V / 0.05C under constant current / constant voltage (CC / CV) conditions at 25°C, and then discharged to 3.0V using 1C under constant current (CC) conditions. This was considered as one cycle, and the test was repeated for 2000 cycles. The capacity retention rate of the 2000th cycle during the charge and discharge process was measured.

[0139] The test results are shown in Table 1:

[0140] Table 1

[0141]

[0142]

[0143] It can be seen from Table 1 that:

[0144] (1) By comparing Example 1 with Comparative Example 4, it is found that by providing a transition component between the active component and the protective component, the active component LiCo 1-x M x PO 4 The concentration of the protective component Li 3 V 2 (PO 4 ) 3 A gradient structure cathode material with a gradually increasing concentration of Figure 2The schematic diagram of the distribution of cobalt and vanadium in the cross section of the positive electrode material obtained in Comparative Example 4 shows that when no transition layer is provided, LiCo and vanadium exist in the positive electrode material only in a small area at the junction of the active component and the protective component. 0.95 Ti 0.05 PO 4 and Li 3 V 2 (PO 4 ) 3 , that is, a core-shell structure is formed, which is not conducive to the transfer of charges and the diffusion of ions; Figure 1 This is a schematic diagram of the distribution of cobalt and vanadium elements in the cross section of the gradient structure positive electrode material obtained in Example 1. It can be seen from the figure that a transition component is provided between the active component and the protective component to form an active component LiCo 1-x M x PO 4 The concentration of the protective component Li 3 V 2 (PO 4 ) 3 The gradient structure positive electrode material with gradually increasing concentration of active ingredients strengthens the binding with the protective ingredient without destroying the lattice structure of the active ingredient, making the transition interface between the two smoother, which is beneficial to improving the charge transfer and ion diffusion process. The prepared positive electrode material has better rate performance and cycle performance.

[0145] (2) By comparing Example 1 with Examples 5-8, it is found that setting a suitable proportion of transition components can effectively form a good gradient structure inside the positive electrode material particles, which is beneficial to the transfer of charges and the diffusion of ions. The prepared positive electrode material has better rate performance and cycle performance.

[0146] (3) By comparing Example 1 with Examples 9-12, it is found that setting an appropriate ratio of protective components can effectively form a protective layer on the outer surface of the active component to prevent the active component inside from directly contacting the electrolyte, thereby improving the stability of the solid-liquid interface. At the same time, the performance of the active component will not be affected by excessive protective components.

[0147] (4) By comparing Example 1 with Examples 13-15 and Comparative Examples 1-2, it is found that the transition layer is doped with an appropriate amount of Ti, which produces defects inside the crystal. These defects are beneficial to the Li + The diffusion of the doped elements and the metal elements in the original lattice is different in charge valence, resulting in a charge difference. Therefore, cation vacancies are formed through the charge compensation mechanism, which improves the conductivity of the material and the rate performance of the material. At the same time, the capacity of the positive electrode material will not be affected by excessive doping elements.

[0148] (5) By comparing Example 1 with Examples 16-20, it is found that setting a suitable V content in the transition component can effectively form a gradient structure inside the positive electrode material particles, giving full play to the LiCo 1-y-z V z N y PO 4 Due to the role of the transition layer, the prepared positive electrode material has better rate performance and cycle performance;

[0149] (6) By comparing Example 1 with Comparative Example 3, it is found that: compared with multi-step sintering, first preparing a doped precursor material (first precursor material) or a multi-layer coated doped precursor material (second precursor material and third precursor material), and then preparing a doped lithium cobalt phosphate positive electrode material with a gradient structure through a one-step high-temperature sintering, it is possible to avoid the damage to the crystal structure of the doped lithium cobalt phosphate caused by the high temperature of multiple sintering, and the prepared positive electrode material has better rate performance and cycle performance.

[0150] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0151] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0152] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0153] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A gradient structure positive electrode material, characterized in that: The gradient structure positive electrode material comprises an active component and a protective component encapsulating the active component; from the inside to the outside of the gradient structure positive electrode material, the concentration of the active component gradually decreases, and the concentration of the protective component gradually increases; The gradient structure positive electrode material further includes a transition component, which is disposed between the active component and the protective component and diffuses toward the active component and the protective component respectively; The active ingredient includes LiCo 1-x M x PO4, wherein M is any one of Ti, Zr, Al or a combination of at least two thereof, 0.01≤x≤0.1; the protective component comprises Li3V2(PO4)3; the transition component comprises LiCo 1-y-z V z N y PO4, wherein N is any one of Ti, Zr, Al or a combination of at least two thereof, 0.01≤y≤0.1, 0.2≤z≤0.

45.

2. The gradient structure positive electrode material according to claim 1, characterized in that: From the inside to the outside of the gradient structure positive electrode material, the concentration of the active component gradually decreases from 100% to 0, and the concentration of the protective component gradually increases from 0 to 100%.

3. The gradient structure positive electrode material according to claim 1, characterized in that: The mass of the active component accounts for 90-98 wt % of the mass of the gradient structure positive electrode material; the mass of the protective component accounts for 2-10 wt % of the mass of the gradient structure positive electrode material.

4. The positive electrode material according to claim 1, characterized in that The mass of the active component accounts for 75-88wt% of the mass of the gradient structure positive electrode material; the mass of the protective component accounts for 2-5wt% of the mass of the gradient structure positive electrode material; the mass of the transition component accounts for 10-20wt% of the mass of the gradient structure positive electrode material.

5. The method for preparing a gradient structure positive electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) adding a phosphorus source to an aqueous solution containing a cobalt source and a metal M source in a molar ratio of (1-x):1, and heating the solution to react to obtain a first precursor material; 0.01≤x≤0.1; (2) adding the first precursor material obtained in step (1) and the phosphorus source to an aqueous solution containing a cobalt source, a vanadium source and a metal N source in a molar ratio of (1-yz):z:y, and heating the mixture to react to obtain a second precursor material; 0.01≤y≤0.1, 0.2≤z≤0.45; (3) adding the second precursor material obtained in step (2) and the phosphorus source to the aqueous solution containing the vanadium source, and heating the mixture to react to obtain a third precursor material; (4) Mixing the lithium source with the third precursor material obtained in step (3) and sintering the mixture under an inert atmosphere to obtain a gradient structure positive electrode material.

6. The preparation method according to claim 5, characterized in that: The temperature of the heating reaction in step (1), step (2) and step (3) is independently selected from 20 to 50°C.

7. The preparation method according to claim 5, characterized in that: The heating reaction time in step (1), step (2) and step (3) is independently selected from 3 to 8 hours.

8. The preparation method according to claim 5, characterized in that: The preparation method further comprises washing and drying the obtained first precursor material, second precursor material and third precursor material in sequence in step (1), step (2) and step (3) respectively.

9. The preparation method according to claim 8, characterized in that: The washing includes washing with water until the pH is neutral.

10. The preparation method according to claim 8, characterized in that: The drying is performed under vacuum.

11. The preparation method according to claim 8, characterized in that: The drying temperature is 80-100° C. and the drying time is 20-30 hours.

12. The preparation method according to claim 5, characterized in that: The sintering in step (4) includes first performing a first sintering and then performing a second sintering.

13. The preparation method according to claim 12, characterized in that: The first sintering is carried out at a temperature of 200 to 300° C. and for a time of 3 to 5 hours.

14. The preparation method according to claim 12, characterized in that: The second sintering temperature is 600-800° C. and the time is 8-15 hours.

15. The preparation method according to claim 5, characterized in that: The inert atmosphere in step (4) includes any one of nitrogen, helium or argon, or a combination of at least two of them.

16. The preparation method according to claim 5, characterized in that: The cobalt source includes any one of cobalt sulfate, cobalt chloride, cobalt nitrate or cobalt oxalate, or a combination of at least two thereof.

17. The preparation method according to claim 5, characterized in that: The metal M source includes any one of titanium sulfate, titanium chloride, titanium nitrate, zirconium sulfate, zirconium chloride, zirconium nitrate, aluminum sulfate, aluminum chloride or aluminum nitrate, or a combination of at least two thereof.

18. The preparation method according to claim 5, characterized in that: The phosphorus source includes ammonium phosphate and / or diammonium phosphate.

19. The preparation method according to claim 5, characterized in that: The vanadium source includes ammonium metavanadate and / or vanadium pentoxide.

20. The preparation method according to claim 5, characterized in that: The lithium source includes lithium hydroxide and / or lithium carbonate.

21. The preparation method according to claim 5, characterized in that: The metal N source in step (2) and the metal M source in step (1) are of the same material.

22. The preparation method according to claim 5, characterized in that: The cobalt source in step (2) is the same material as the cobalt source in step (1).

23. The preparation method according to claim 5, characterized in that: The vanadium source in step (2) is the same material as the vanadium source in step (1).

24. The preparation method according to claim 5, characterized in that: The phosphorus sources in step (1), step (2) and step (3) are the same material.

25. A positive electrode sheet comprising the gradient structure positive electrode material according to any one of claims 1 to 4 or the gradient structure positive electrode material obtained by the preparation method according to any one of claims 5 to 24.

26. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet according to claim 25.

Citation Information

Patent Citations

  • Preparation method of nano-fibrous lithium cobalt phosphate positive electrode material

    CN103956486A

  • Graphene composite carbon-coated cobalt-lithium phosphate material and preparation methods and application thereof

    CN105576204A

  • Preparation method and application of positive electrode material of lithium ion battery

    CN106207138A

  • Gradient composite solid electrolyte, preparation method thereof and solid-state lithium battery

    CN110931849A